Slant Strategy and Multimedia Integration in EFL Listening: A Quantum Teaching Framework - Asriadi Rasyid; Ilham Sahabuddin; Salasiah; Suhria; Nur Fahmi Akhmad (Universitas Islam Negeri Palopo, 2026)
This study investigates the effectiveness of integrating the SLANT strategy an active listening approach that promotes students’ attention and engagement with multimedia tools within a Quantum Teaching framework to improve students’ listening comprehension. A quasi-experimental design was conducted with 60 second-grade students at SMP Negeri 2 Parepare, divided into experimental and control groups. Data were obtained through listening comprehension tests, questionnaires, and observation checklists. The findings revealed a statistically significant difference in listening comprehension performance between the two groups, with students in the experimental group achieving higher scores than those in the control group. The results indicate that the integration of the SLANT strategy and multimedia within the Quantum Teaching approach effectively enhances listening comprehension in EFL classrooms. This study provides empirical support for the use of interactive and multimodal instructional strategies to strengthen students’ listening skills.